ASSOCIATION BETWEEN SEXUAL ORIENTATION AND CONDYLOMA ACUMINATA IN HIV PATIENTS AT TERTIARY REFFERAL HOSPITAL IN LAMPUNG PROVINCE - Dwi Indria Anggraini; Muhammad Syafei Hamzah; Hendra Tarigan Subero; Yulisna Yulisna; Yustisya Khoirunnisa (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Condyloma acuminata is one of the most common sexually transmitted infections caused by the Human Papilloma Virus. Condyloma acuminata has been reported in many patients with Human Immunodeficiency Virus (HIV). Several studies have reported the factors associated with the incidence of condyloma acuminata in HIV, but it has never been reported the factors affected condyloma acuminata in Lampung Province. This study aimed to determine the relationship between sexual orientation and condyloma acuminata in HIV patients at RSUD Dr. H. Abdul Moeloek Lampung Province. The design of this study was an observational study with a case control design with a sample of 112 HIV patients. The sample of the study was new patients diagnosed with HIV who were treated at RSUD Dr. H. Abdul Moeloek Lampung Province in the period 2017 to 2019. Data were obtained from patient medical records. The results showed that 36 (64.3%) HIV/AIDS patients with condyloma acuminata had a homosexual orientation. Data analysis using Chi-square test showed the p value was 0.01. The conclusions of this study indicate that there is an association between sexual orientation and condyloma acuminata in HIV/AIDS patients.